Characteristics of detected and undetected dementia among community‐dwelling older people in Metropolitan Tokyo. Issue 6 (15th April 2020) - Ura, Chiaki; Okamura, Tsuyoshi; Inagaki, Hiroki; Ogawa, Madoka; Niikawa, Hirotoshi; Edahiro, Ayako; Sugiyama, Mika; Miyamae, Fumiko; Sakuma, Naoko; Furuta, Ko; Hatakeyama, Akira; Ogisawa, Fumiko; et al.
Abstract : Aim: Although a series of policies have been adapted to deliver an early diagnosis of dementia, many people living with dementia remain undetected and undiagnosed. The aim of this study is to investigate the characteristics of undetected dementia in community‐dwelling older people in Metropolitan Tokyo. Methods: We conducted a three‐step survey. First, the questionnaires were mailed, in total, to 7614 residents aged ≥70 years in one area in Tokyo, and 5430 were retrieved. Secondly, 2020 individuals attended the face‐to‐face survey, including Mini‐Mental State Exam (MMSE). Thirdly, 198 of 335 individuals who scored <24 on MMSE were visited. Diagnosis of dementia, Clinical Dementia Rating and need for social support were assessed by the interdisciplinary team at their home, and psychological variables, sociological variables and sociodemographic variables were evaluated. Results: Among the 198 participants, 78 (39.4%) were assessed to have dementia. Among those who had dementia, 34 had received a previous diagnosis of dementia in a clinical setting, i.e., the rate of undetected dementia among our 198 participants was 56.4%. People living with dementia without a dementia diagnosis tended to have more complex social support needs, particularly in the domains of dementia diagnosis, medical check‐ups for physical conditions, continuous medical care and housing support. In addition, they exhibited signs of frailty. Conclusions: Given that people living with dementia without a dementia diagnosis are at risk of losing housing or physical health, it is a threat to human rights. Geriatr Gerontol Int ; : – Geriatr Gerontol Int 2020; : – .